2020
DOI: 10.3390/ma13153318
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Microcrack Orientation Using the Directivity of Secondary Sound Source Induced by an Incident Ultrasonic Transverse Wave

Abstract: In this paper, characterization of the orientation of a microcrack is quantitatively investigated using the directivity of second harmonic radiated by the secondary sound source (SSS) induced by the nonlinear interaction between an incident ultrasonic transverse wave (UTW) and a microcrack. To this end, a two-dimensional finite element (FE) model is established based on the bilinear stress–strain constitutive relation. Under the modulation of contact acoustic nonlinearity (CAN) to the incident UTW impinging on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
(49 reference statements)
1
6
0
1
Order By: Relevance
“…Two-layer meshes are introduced to simulate the existence of the microcrack examined. The model is similar to the one reported in the authors' previous work, [34] with differences in terms of geometry and driving frequencies of primary waves.…”
Section: Fe Modelsupporting
confidence: 77%
See 1 more Smart Citation
“…Two-layer meshes are introduced to simulate the existence of the microcrack examined. The model is similar to the one reported in the authors' previous work, [34] with differences in terms of geometry and driving frequencies of primary waves.…”
Section: Fe Modelsupporting
confidence: 77%
“…[32] In this case, the microdamage can be deemed as the secondary sound source (SSS) radiating wave components with frequencies different from that of primary waves. [33,34] So far, considerable efforts have been made on nondestructive testing of microdamage by using the wave mixing method. Ding et al proposed a method for locating the microcrack region by calculating the start and end time of time-domain signals of the resonant waves.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been reported that the nonlinear ultrasonic scattering can be dependent on the incident angle. 40,[52][53][54][55][56] Note that most of the studies on the incidentangle dependence of nonlinear ultrasonic scattering have been limited to theoretical ones. Although the development of a PA controller and an array transducer for higher-voltage excitation voltage is required to input a large-amplitude incidence for oblique incidence, further experimental study for elucidating the relationship between the incident angle and nonlinear ultrasonic scattering will be exciting topics from practical and physical perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…数相关性不大。 类似地, Li 等人 [66] 研究了三层胶粘结构中粘接层随机分布微裂纹对非线性 Lamb 波传播的影响,粘接层微裂纹会生成 Lamb 波二次谐波,且非线性参量随微裂纹区域大小和微 裂纹密度的增加而增加。对于非线性 Lamb 波混频响应,Yin 等人 [67] 研究发现,板中随机分布 微裂纹可以生成 Lamb 波和频和差频信号。非线性参量对微裂纹密度有很强的依赖性,当密度 不变时,非线性参量随微裂纹区域的增大呈线性增加。 (4)方向 在二次谐波方面,Yang 等人 [50] 对不同裂纹长度的疲劳裂纹产生 Lamb 波二次谐波的方向性 开展了仿真研究,如图 5 所示。研究发现,疲劳裂纹产生的二次谐波主要分布在裂纹前向和后 向的散射方向, 且仅前向散射方向的二次谐波幅值随裂纹长度的增大而单调增大。Wang 等人 [68] 研究了横波与微裂纹相互作用生成二次谐波的方向性,结果表明,二次谐波的方向性随微裂纹 取向角的变化而变化。在非线性混频方面,Lv 等人 [69] 数值分析了两列横波和裂纹之间的非共线 混频作用,结果表明,生成最大混频纵波幅值对应的两列横波相互作用角与裂纹的方向相关。 Lv 等人 [70] 分析了两列 A0 模式 Lamb 波与微裂纹的非线性混频作用,结果表明,两列 A0 模式 Lamb 波与微裂纹相互作用产生了透射和反射和频 S0 模式 Lamb 波, 两种和频 S0 模式 Lamb 波 的传播方向随微裂纹方向的变化呈现不同的趋势:透射和频的传播方向角与微裂纹的取向基本 一致,而反射和频的传播方向角则随微裂纹的取向线性增加。 图 5 疲劳裂纹归一化非线性参量的方向性 [50] Figure 5 Directivity pattern of normalized nonlinear parameters for fatigue cracks [50] 此外,关于接触压力对裂纹非线性的影响也有报道 [71][72][73] 。Yang 等人 [71] 研究了拉伸载荷作用 下裂纹面张开对不同长度疲劳裂纹非线性响应的影响,结果表明,施加在板上的载荷能明显改 变裂纹的非线性响应。Saidoun 等人 [72,73] 分析了纵波与单向接触界面的相互作用,建立了界面接 触压力与生成二次谐波的对应关系,结果表明,随着界面接触压力的增加,二次谐波先增加后 减小。 A c c e p t e d https://engine.scichina.com/doi/10.1360/TB-2021-0798…”
Section: 入射波方式和不同裂纹角度进行模拟,研究了切向接触和法向接触对裂纹非线性的影响。unclassified